Kinerja Ombudsman Perwakilan Riau Dalam Penanganan Keluhan Pelayanan Publik Di Bidang Pendidikan Di Kota Pekanbaru - Wella Mastri Aidhila; Dadang Mashur (Bahasa Indonesia, 2022)
With the occurrence of maladministration in education in Pekanbaru City, the Ombudsman has the authority to oversee the implementation of public services at educational institutions in Pekanbaru City. Quality education is a goal that is in line with Law no. 20 of 2003 that the national education system must ensure equal distribution of educational opportunities, quality improvement. This research is to find out how the performance of the Ombudsman Representative of Riau in handling complaints of public services in the field of education and what are the inhibiting factors for the performance of the Ombudsman. The theory used in the study is the performance measurement indicator Agus Dwiyanto (2006). The method used is qualitative with a descriptive approach through interviews, observations, and documentation. The result of the research is that the performance of the Riau Representative Ombudsman is quite good. The factors that hinder the performance of the Ombudsman Representative in Riau are the lack of human resources, lack of budgetary resources, and lack of facilities and infrastructure.